A GCH1 haplotype confers sex‐specific susceptibility to pain crises and altered endothelial function in adults with sickle cell anemia. Issue 2 (February 2014) - Belfer, Inna; Youngblood, Victoria; Darbari, Deepika S.; Wang, Zhengyuan; Diaw, Lena; Freeman, Lita; Desai, Krupa; Dizon, Michael; Allen, Darlene; Cunnington, Colin; Channon, Keith M.; Milton, Jacqueline; et al.
<x xml:space="preserve">Abstract</x> GTP cyclohydrolase (GCH1) is rate limiting for tetrahydrobiopterin (BH4) synthesis, where BH4 is a cofactor for nitric oxide (NO) synthases and aromatic hydroxylases. GCH1 polymorphisms are implicated in the pathophysiology of pain, but have not been investigated in African populations. We examined GCH1 and pain in sickle cell anemia where GCH1 rs8007267 was a risk factor for pain crises in discovery (n = 228; odds ratio [OR] 2.26; P = 0.009) and replication (n = 513; OR 2.23; P = 0.004) cohorts. In vitro, cells from sickle cell anemia subjects homozygous for the risk allele produced higher BH4. In vivo physiological studies of traits likely to be modulated by GCH1 showed rs8007267 is associated with altered endothelial dependent blood flow in females with SCA (8.42% of variation; P = 0.002). The GCH1 pain association is attributable to an African haplotype with where its sickle cell anemia pain association is limited to females (OR 2.69; 95% CI 1.21–5.94; P = 0.01) and has the opposite directional association described in Europeans independent of global admixture. The presence of a GCH1 haplotype with high BH4 in populations of African ancestry could explain the association of rs8007267 with sickle cell anemia pain crises. The vascular effects of GCH1 and BH4 may also have broader implications for cardiovascular disease in populations of African ancestry. Am. J. Hematol. 89:187–193, 2014. © 2013 Wiley Periodicals, Inc.